A Study of the Rich History of the Baltic Sea Countries - Sven Ekdahl (Fasciculi Archaeologiae Historicae)
The article in memory of Professor Tadeusz Poklewski-Koziełł gives an outline of the history of the Baltic Sea and the surrounding states with the sea as a unifying and sometimes separating element. It is a panoramic view, focusing especially on older history. The presentation begins with an overview of the Baltic Sea as a brackish sea and its individual character in comparison with other seas. This is followed by sections on prehistoric times and Viking Age, the Hanse, the Teutonic Knights and the Livorian War in the second half of the 16th c. Not only Poles, Lithuanians, Russians, and Germans were involved, but also Danes and Swedes. Of great importance for the coming development was the Swedish dream of a Dominium maris Baltici, which was indeed realized in the 17th c., but then turned out to be unrealistic. After the loss of Finland to Russia in 1809, Sweden was reduced to its present size, while Russia and Prussia ascended to new major powers in the Baltic region. In the late 18th c. the great power Poland-Lithuania (Rzeczpospolita) was dismembered into three parts. Art and culture however flourished, despite oppression. In addition to the presentation of political events, views of trade and markets, architecture, cartography, shipbuilding, navies, dynastic questions etc. are also sporadically presented. The article concludes with some personal remarks with reference to the ecology of the Baltic Sea and the Baltic Sea region. The hope is expressed that the many problems with pollution may be brought in the public eye according to the spirit of the Baltic Marine Environment Protection Commission, also known as the Helsinki Commission (HELCOM)